(3EeYGf GdfXQs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdhGgH cd ehghH ef GdeQUhO hGdebUhObhdg GdMeO ddg GdhGgH ddeDefjf SHjd GdUhGH ddMeO eYfi dZhj gh GdhUa HGdLejds
(3BNQgG (B:s
(3aj cdeI hGMOI ceG aj HGH GSJhi hGdMed Ydi fXjQg Ch fbjVg hchf MQcI eG bHdgG aj Mce GdSchf hZjQ Pdc eeG Hjf aj GdeWhdGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 61s
(3eYLe GdeDdajf(B: 3 / 176s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdUQas